Changes in Anatomic Risk Factors for Patellar Instability During Skeletal Growth and Maturation. Issue 9 (July 2022) - Pruneski, James; O'Mara, Lauren; Perrone, Gabriel S.; Kiapour, Ata M.
Background: Several anatomic risk factors have been identified in the pathogenesis of patellofemoral instability. The literature is sparce regarding how these anatomic risk factors change during skeletal growth and development. Hypothesis: The anatomic risk factors associated with patellar instability change significantly during skeletal growth and maturation with different patterns in male versus female patients. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Magnetic resonance imaging data from 240 unique, asymptomatic knees (7-18 years of age; 50% female) were used to measure patellar height (Caton-Deschamps index), lateral patellar tilt angle, trochlear height, trochlear groove depth, trochlear sulcus angle, and tibial tubercle–trochlear groove (TT-TG) distance. Linear regression was used to test the associations between age and anatomic findings. Two-way analysis of variance with Holm-Šídák post hoc test was used to compare anatomic characteristics between sexes in 3 age groups: prepubertal school-aged children (7-10 years old), early adolescents (11-14 years old), and late adolescents (15-18 years old). Results: Patellar height (female sex), lateral patellar tilt angle (male sex), and trochlear sulcus angle (both sexes) decreased with age ( P < .001). Trochlear height, depth, and TT-TG distance increased with age in both male and female participants ( P < .02). Male participants had a larger sulcus angle (by 5.3°± 1.6° at age 11-14 years) and greater trochlear height (by >5 mm across medial, central, and lateral regions at age 15-18 years) than age-matched female participants ( P < .01). We found no other sex-related differences in quantified anatomic features ( P > .1). Conclusion: The findings partially support our hypothesis indicating significant age-related changes in all quantified features, which were not different between male and female participants except for trochlear sulcus angle in early adolescence and trochlear height in late adolescence. In general, the majority of anatomic risk factors for patellar instability change with maturity in a direction that assists in reducing the risk of patellar instability and/or dislocation. The only outlier is the TT-TG distance, which increased by age, and in our oldest cohort of patients, the mean fell below the normal adult range. The current observations highlight the importance of age in the interpretation of risk for injury as well as the need for further studies to identify intrinsic and extrinsic factors that may result in abnormal development of these anatomic features during skeletal growth and maturation.